The Theory and Praxis of War and Peace in the Thucydidian Era: 450-400 BC - Arnopoulos, Paris (Études helléniques / Hellenic Studies, 1998)
This article presents the salient exopolitical ideas and acts of the Greeks in their Golden Age at the latter half of the fifth century. In order to put this particular place and time in its proper general perspective, this study juxtaposes the relevant theories and practices involved in the great events, which shook the epicenter of the ancient world. At that time, the defining activity of inter-city-state relations was the Peloponnesian War as recorded in the monumental History of Thucydides. This work, together with those of other great thinkers of that fateful era give us an idea of the perennial dilemma between patriotism and nationalism, as well as idealism and realism. The working hypothesis here is that these issues may be discussed and resolved dialectically, so that their resulting synthesis explains many classic and current contradictions in macro politics.